(untitled) (Italian Review of Legal History, 2020)
The essay contributes to a wider ongoing research and aims to offer a first critical patrol on the historical-juridical aspects of the anti-monarchy doctrine. Specifically, it points out this doctrine’s late Renaissance roots (§ 2), which present continuous and juridically relevant recalls to “caesaricide” (§ 3), and discloses the complex historical-political dynamics of modern religious strifes (Reformation and Counter-reformation) as a fertile ground of the pro-tyrannicide theories strong development (§§ 4-6). After underlining the question’s reconfiguration in light of modern jusnaturalism, the essay halts at the beginning of the 18th century with the peculiar Enlightenment approach (§ 7).